Power play the beginning of the endgame in Net markets - Moriarty, Mike (Wiley, 2001)
In this important book, a team of experts from the prestigious international consulting firm of A. T. Kearney offer powerful insights and analysis of the business and financial opportunities opening up in the B2B landscape. Drawing upon A. T. Kearney's groundbreaking consulting work on B2B issues with top companies around the globe, they develop a framework for understanding the implications and competitive advantages of B2B now and in the years ahead. And, with the help of real-life examples and case studies from Microsoft, Intuit, Nabisco, and other major U.S., European, and Asian players in the consumer, automotive, and high-tech industries, they outline proven strategies and tactics managers can use to enter and make the most of the B2B space.